The diminishing of supernatural beliefs: a case of Bujang Valley, Merbok / Maznah Wan Omar ... [et al.] - Wan Omar, Maznah; Mohammed, Syakirah; Ibrahim, Syazliyati (2018)
In the olden days, Malay communities in Lembah Bujang, Kedah have strong beliefs towards supernatural beings. The concept of interdependence between human and supernatural beings started as job task was solely dependent on human strength. Technology was unknown during those days which force some people to seek help from supernatural beings. Religious beliefs were shaky, and animistic was the in thing. The methodology adopted in this study was through the adoption of the oral history method and was found deemed appropriate for this type of study. This phenomenon has gone through great revolution when the Islamic religion was introduced and communities learn about Islamic concept through Islamic teaching and learning in mosque and now books and materials on Islamic religion can be obtain easily through which changes the belief and culture of the Lembah bujang communities. The belief in the supernatural, though inherent among the residents of the Bujang Valley in the early 20th century, began to diminish towards the latter half of the century with better understanding and appreciation of Islam.